The Importance of Academic Supervision for Primary School Teachers: Insights from Educators in Rural Indonesia - Widatin, Tri; Roemintoyo, Roemintoyo; Sukarno, Sukarno (Universitas Sebelas Maret, 2025)
Academic supervision plays a strategic role in enhancing the quality of learning in elementary schools. However, in rural schools, the practice of supervision tends to be predominantly administrative, with an evaluative approach that inadequately supports the ongoing professional development of teachers. This study aims to explore the perceptions of teachers and school principals regarding academic supervision and to describe the practices and challenges of its implementation in the context of rural elementary schools. The research employs a descriptive qualitative approach, utilizing semi-structured interviews and document analysis for data collection. The informants include one principal and five teachers from SD Negeri 2 Jurug, Boyolali, Central Java. Data were analyzed using an interactive thematic approach, involving data reduction, presentation in matrices, and conclusion drawing, with triangulation to ensure validity. The findings indicate that perceptions of supervision are divided between administrative control functions and professional development, with implementation remaining procedural and lacking follow-up actions. The main challenges include time constraints, the dual role of the principal, and poor communication quality. The implications of this research underscore the necessity for a transformation in supervision towards a more reflective, contextual, and coaching-based approach.